The Effect of North Refineries Company on Soil pollution of Baiji City-Iraq - Al-Dabbas, Moutaz; Hussain, Ghazi; Al-Jubory, Mahmmod (Iraqi Journal of Science, 2023)
The average concentrations of heavy metals (Pb, Co, Ni, Cr, Cd and Zn) in soil of North Refineries Company (NRC) at Baiji and around were determined in 29 selected locations using GPS. The pickings up of samples were carried out in three periods in 2012 in January, March and July. The concentration levels of determined heavy metals shows values within or lower than many researchers.The model of cumulative effect of the heavy metals, which was determined by GIS for the triple sampling periods show distribution of concentration towards wind directions and away from the site of NRC e.g. SE direction. This indicates the meteorological conditions represented by the wind direction and the rainfall, which plays an important role in distribution and deposition of pollutant metals via water drainage of the area.